A Review on Plants and Plant/Microbial Systems in Reducing Exposure - Niazi, Parwiz; Monib, Abdul Wahid; Azizi, Azizaqa (Journal for Research in Applied Sciences and Biotechnology, 2023)
Plants and plant-microbial compounds can be a viable means of remediating contaminated soils, in this review, two approaches to phytoremediation are discussed, the first approach how plants can promote the growth of degrading microorganisms in the soil rhizosphere, which can lead to enhanced degradation of chlorinated pesticides; the second approach focuses on the potential of plants to remove and accumulate metals from their environment, a unique test system, the Target Neighbor Method, is used to evaluate how plant density affects metal uptake, these studies could provide valuable information for optimizing plant density to improve metal removal and remediate metal-contaminated soils or to minimize toxic metal accumulation in crops and reduce human exposure.